Descent trajectory reconstruction and landing site positioning of Chang’E-4 on the lunar farside - Jianjun Liu (Nature Portfolio, 2019)
The Chang’E-4 mission in January 2019 had the major challenge to land on the lunar far side without traditional radiometric techniques due to the missing line-of-sight. The authors here describe landing trajectory reconstruction and positioning techniques based upon the Moon’s digital terrain model that allowed reproducing the entire process of a successful landing.